2019
DOI: 10.1021/acs.nanolett.9b03460
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Rh Species with NiFe-Layered Double Hydroxide for Overall Water Splitting

Abstract: NiFe-layered double hydroxide (LDH) is thought of as a promising bifunctional water-splitting catalyst, owing to its excellent performances for alkaline oxygen evolution reactions (OERs). However, it shows extremely poor activity toward hydrogen evolution reactions (HERs) due to the weak hydrogen adsorption. We demonstrated that the integration of Rh species and NiFe-LDH can dramatically improve its HER kinetics without sacrificing the OER performance. The Rh species were initially integrated into NiFe-LDH as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(89 citation statements)
references
References 53 publications
1
87
1
Order By: Relevance
“…In addition, we applied the DFT-D3 (BJ) method to evaluate the van der Waals (vdW) effect in all calculations. The Gibbs free energy of the intermediates for HER and OER process, that is, H, OH, O, and OOH, can be calculated as 75,76 ΔG ¼ E ads þ ΔE ZPE À TΔS ð1Þ…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we applied the DFT-D3 (BJ) method to evaluate the van der Waals (vdW) effect in all calculations. The Gibbs free energy of the intermediates for HER and OER process, that is, H, OH, O, and OOH, can be calculated as 75,76 ΔG ¼ E ads þ ΔE ZPE À TΔS ð1Þ…”
Section: Discussionmentioning
confidence: 99%
“…The Gibbs free energy of the intermediates for HER and OER process, that is, H, OH, O, and OOH, can be calculated as 75 , 76 where E ads is the adsorption energy of intermediate, Δ E ZPE is the zero point energy difference between the adsorption state and gas state, T is the temperature, and Δ S is the entropy various between the adsorption and gas phase. For adsorbates, E ZPE and S are obtained from vibrational frequencies calculations with harmonic approximation and contributions from the slabs are neglected, whereas for molecules these values are taken from NIST-JANAF thermochemical Tables 77 .…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, the formation of heterostructures between LDHs and metal nanoparticles is considered beneficial to enhance OER activity. Francisco and coworkers integrated Rh species with NiFe LDH, whereas Rh acts as oxidized dopants and metallic clusters (< 1 nm), which can dramatically improve OER kinetics with overpotential 7 and 35 mV smaller than that of NiFe LDH at 10 and 100 mA cm ‒2 , respectively [ 98 ]. Song et al reported a facile one-step method synthesizing Ru atoms supported on a monolayer NiFe LDH with precise location instead of random dispersion [ 99 ].…”
Section: Structure Modulation Toward Application In Oxygen Evolution Reactionmentioning
confidence: 99%
“…Compared with single‐phase catalysts, hybrid catalysts with the anchored precious metal nanoparticles always possess much better activity due to the modulated electrical structures on the interfaces. [ 86–88 ] In another interesting work, Du et al. [ 89 ] reported the synthesis of a series of ultrathin Co(OH) 2 nanosheets anchored with ultrafine alloy nanoparticles (≈1.6 nm) by the top‐down dealloying strategy.…”
Section: Corrosion Engineering Enabled Electrocatalystsmentioning
confidence: 99%